Rhétorique des figures et rhétorique des conflits; entre stylistique et argumentation - Domańska-Gruszka, Jolanta (Studia Romanica Posnaniensia, 2007)
The term of rhetoric has known several senses since its foundation as techne of persuasion by Aristote. This paper presents the historical reasons of limitation of the first rhetorical project into the scholar treaties in 17th-19th centuries. The next question is to explain the revival of rhetorical tradition with Chaim Perelman Olbrechts-Tyteca Traité de l'argumentation focused on the theory of argumentation and the French "nouvelle critique" focused on linguistics and stylistics. The key-term for both linguistic and philosophic approach of new rhetoric is a figure of speech. The author tries to find out if the modem reunified vision of rhetoric is possible and suitable.